(3WQaI GdCUMGH aj eYQaI GdCfSGHs - (3YeQ Hf jhSa Hf YeQ Hf Ydj Hf QShd, CHh MaU, eegO GdOjf, Gdedc GdCTQa,J (B696 (3g` s
(3ChdgG (B:s
(3aEf gPG eNJUQ jTgO MaXg QYdi Chdi GdCdHGH , eMJh Ydi CfSGH Phi GdbQH s
(3BNQgG (B:s
(3hCgd YHOGddg JTjNge ebHd Hf YOGdg , hGQcGeI TjNge Ydi Hf CfYe hgh jQLY GdLejY ef gDdGA Edi CjhH GdPj ai OKjfg ,, agPG eG GJUd Gdjg GdHMK s
(3Vef eLehY , JQJjHgG (B: (3ef U (B79 - (3U(B95s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B6s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B901 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B283 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs